Diagnosis, Prevention and Treatment for Stroke - Katsanos, Aristeidis H. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In recent years, there have been outstanding achievements in stroke diagnosis and care. Our better understanding of the pathophysiological mechanisms and the advances in neuro-imaging have enabled us to diagnose stroke syndromes with remarkable precision and uncover underlying vessel pathologies that can be directly correlated to the stroke event. Within a short period of time, mechanical thrombectomy became the standard of care for patients with large vessel occlusions and symptom onset up to 24 hours, while other recent trials also suggest the use of perfusion imaging to guide intravenous thrombolysis in the extended time window. In this Special Issue, we will also extensively discuss relevant topics on secondary stroke prevention, including the prompt use of nonvitamin k oral anticoagulants and the potential effect of reversal agents in patients with intracerebral hemorrhage related to their use. We will also delineate treatment options for stroke patients with indication for long-term anticoagulation and high bleeding risk. Finally, a particular mention will be made for young patients with stroke, the extent of the diagnostic work-up, and the selection of those who would benefit from patent foramen ovale closure.